Inhibition of farnesyl pyrophosphate synthase prevents angiotensin II-induced cardiac fibrosis in vitro. (24th April 2014) - Li, Z; Bi, X; Wang, M; Zhang, J; Song, J; Shen, X; Han, J; Fu, G; Ye, Y
Summary: Farnesyl pyrophosphate synthase (FPPS)-catalysed isoprenoid intermediates are important for the activation of Ras homologue gene family, member A (RhoA) in angiotensin (Ang) II-induced cardiac fibrosis. This study was designed to investigate the specific role of FPPS in the development of cardiac fibrosis. We demonstrated that FPPS expression was elevated in both in-vivo and in-vitro models of Ang II-mediated cardiac fibrosis. FPPS inhibition by zolendronate and FPPS knock-down by a silencing lentivirus decreased the expression of cardiac fibrosis marker genes, including collagen I, collagen III and transforming growth factor (TGF)-β1. FPPS inhibition was reversed by geranylgeraniol (GGOH) and mimicked by RhoA knock-down with siRhoA. The antagonistic effect of GGOH on the zolendronate-mediated modulation of RhoA activation in Ang II-stimulated cardiac fibroblasts was demonstrated by a pull-down assay. Furthermore, FPPS knock-down also prevented RhoA activation by Ang II  in vitro . In conclusion, FPPS and RhoA may be part of a signalling pathway that plays an important role in Ang II-induced cardiac fibrosis in vitro .